Analisis Kesalahan Siswa dalam Menyelesaikan Soal Persamaan Elips Ditinjau dari Literasi Numerasi pada Level Kognitif Pemahaman, Penerapan dan Penalaran - Diana, Hafsah Adha (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze students’ errors in solving ellipse equation problems in terms of numeracy literacy at the cognitive levels of understanding, application, and reasoning. The research employed a descriptive qualitative method with three twelfth-grade students from SMAS Islam PB. Soedirman Bekasi selected through purposive sampling. Data were collected through essay tests consisting of three numeracy problems on ellipse equations and interviews to confirm students’ answers. Data analysis was carried out through data reduction, data display, and conclusion drawing. The findings revealed that errors at the understanding level were related to students’ inability to grasp concepts, inaccuracies in recognizing facts in the form of symbols and notations, mistakes in processes and procedures, and difficulties in extracting information from tables. At the application level, students demonstrated weaknesses in selecting appropriate strategies, misapplied concepts and procedures, and misinterpreted information from the problems. At the reasoning level, students were unable to analyze information provided in the problems, failed to connect multiple concepts, did not employ suitable strategies, and did not generate alternative solutions. Furthermore, they were unable to draw proper conclusions and presented flawed mathematical arguments in their justifications.